Digital Talent and Innovation Culture as Predictors of Employee Retention in Manufacturing Companies - Astria Alifah Kusumah; Rahma Eka Rianti (Review: Journal of Multidisciplinary in Social Sciences, 2026)
This research aims to analyze the influence of digital talent and innovation culture on employee retention in Indonesian manufacturing companies undergoing digital transformation in the post-pandemic context and Great Resignation phenomenon. Employing a quantitative approach with a causal cross-sectional design, data were collected via Likert-scale questionnaires from manufacturing employees involved in digital technology usage, and analyzed using PLS-SEM to test direct and indirect relationships among variables. Digital talent is operationalized through technical capabilities, technology adaptation skills, and involvement in digital transformation initiatives; innovation culture is measured by organizational support for creativity, measured risk-taking, openness to change, and collaboration with continuous learning; while employee retention is reflected through intention to stay, organizational commitment, and perceptions of career development opportunities. The research model examines the direct effects of digital talent on employee retention, digital talent on innovation culture, innovation culture on employee retention, and the mediating role of innovation culture in the digital talent-employee retention relationship. These findings enrich the strategic human resource management literature in the manufacturing sector and provide practical recommendations for companies in designing holistic and sustainable digital talent retention strategies in the Industry 4.0 era.​